Innovative application of recombinant traditional visual elements in graphic design (Informatica, 2022)
Excellent graphic design can enhance the attractiveness of promotional products. This paper briefly introduces traditional visual elements and their main application methods. Three graphic designs used for promoting Fengxiang painted clay sculpture were analyzed using the analytic hierarchy process method, and a convolutional neural network (CNN) was used for auxiliary analysis. The results showed that the performance of the trained CNN was initially verified in the training set. The comparison between the evaluation results of the three graphic designs and the manual evaluation results further verified the performance of the CNN in aiding the evaluation of the graphic design. All three graphic designs proposed in this paper effectively deconstructed and recombine the traditional visual element, “painted clay sculpture”, enhancing its attractiveness.